Measuring English Teacher’s Evaluation Test - Damayanti, Alfina; Putri, Lisda Asiyah; Munawir, Andi; A., Yuliana; Musdalifa, Musdalifa (JOLIES : Journal of Linguistic and English Studies, 2024)
This article aims to investigate the measurement of English teachers' evaluation tests and results using interviews as the main method of data collection. Interviews were used by the researchers as a tool to help measurement of the evaluation test results. This research involved 1 English teacher. The researchers conducted this research at a state high school in Sorong City. The Data were collected using interview. There were 5 questions given to the teacher. After collecting the data, the researchers separated and analyzed the data descriptively than put them into each items of evaluation test. The result of this result showed that the problem commonly occur the evaluation tests such as teachers who do not master the subject matter, lack of motivation, generalizing students' abilities and questions. Evaluation tests also provide benefits or impacts for students and teachers. The students can find out the value that they have obtained after doing the evaluation test, while the teacher can improve the questions for the evaluation test that will be carried out next.